Research on the Dissemination, Current Situation and Path of Intangible Cultural Heritage under the Background of Digitalization - Chen, Biyu (International Journal of Social Sciences and Public Administration, 2024)
The evolution of digital communication modalities for China’s intangible cultural heritage serves to broaden communication avenues and engage wider audiences, further unlocking the economic potential of the heritage industry. This progression is crucial for advancing the digitization of ICH during the 14th Five-Year Plan in China. Derived from the collective efforts of working individuals over extended periods of production and labor, each intangible culture possesses unique transmission traits. Representing an immaterial and irreplicable historical artifact, cultural memory, and the essence of the Chinese nation, its preservation and transmission are paramount for societal development. Given its profound regional character, the cultural significance and value of ICH are inherently evident. Amidst the mobile internet era, the digital preservation of this heritage has gained precedence, encompassing digital collection, storage, restoration, reproduction, exhibition, and dissemination. However, due to knowledge constraints and technological limitations, non-lineal inheritors face challenges in digitizing ICH.